PCI at the Caribbean Heart Institute - Vinall, Phil (MD Conference Express, 2014)
The first percutaneous coronary intervention (PCI) was performed in the mid-1970s; however, PCI has been available in Guyana only since 2006. The Caribbean Heart Institute (CHI), a 5-bed inpatient facility with 1 catheterization lab, 1 resident cardiologist, 2 internists, and 12 nurses, was the first center in Guyana to perform PCI. This article presents results of a case series that assessed the clinical outcomes of all cases in whom percutaneous transluminal coronary angioplasty or stenting was attempted between January 1, 2011, and June 30, 2013.